2020
DOI: 10.1002/aenm.201903423
|View full text |Cite
|
Sign up to set email alerts
|

Atomic‐Scale Spacing between Copper Facets for the Electrochemical Reduction of Carbon Dioxide

Abstract: Copper (Cu) offers a means for producing value‐added fuels through the electrochemical reduction of carbon dioxide (CO2), i.e., the CO2 reduction reaction (CO2RR), but designing Cu catalysts with significant Faradaic efficiency to C2+ products remains as a great challenge. This work demonstrates that the high activity and selectivity of Cu to C2+ products can be achieved by atomic‐scale spacings between two facets of Cu particles. These spacings are created by lithiating CuOx particles, removing lithium oxides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 60 publications
(100 reference statements)
1
26
0
Order By: Relevance
“…Numerous methods have been intensively explored to achieve this goal. Exposing the CO-preferred binding sites, engineering defects, 34,[52][53][54] controlling the oxidation state, adding promotors for CO binding and regulating the CO binding strength via substrate effects 55,56 were summarized. These methods will be discussed in detail in the following sections.…”
Section: Adsorption Strength Regulationmentioning
confidence: 99%
“…Numerous methods have been intensively explored to achieve this goal. Exposing the CO-preferred binding sites, engineering defects, 34,[52][53][54] controlling the oxidation state, adding promotors for CO binding and regulating the CO binding strength via substrate effects 55,56 were summarized. These methods will be discussed in detail in the following sections.…”
Section: Adsorption Strength Regulationmentioning
confidence: 99%
“…The exposed surface sites of Cu nanomaterials are associated with the binding strength of intermediates, further affecting the catalytic selectivity toward desired products. [ 183–185 ] Sargent and coworkers synthesized Cu catalyst via in situ electrodeposition of copper under CO 2 reduction conditions, which preferentially exposed and maintained Cu(100) facets. [ 183 ] The Cu(100)‐rich catalyst favors the formation of C 2+ products, achieving a constant C 2 H 4 selectivity for 65 h. Huang et al.…”
Section: Mechanism Of Localized Surface Plasmon Resonance‐mediated Reactions For Cu‐based Photocatalystsmentioning
confidence: 99%
“…explored the structure activity of (100), (110), and (111) facets of Cu NPs toward WGS, indicating that the reaction rate of Cu NCs enclosed with {100} facets is almost 5 times than that of Cu octahedra enclosed with {111} facets up to 548 K. [ 184 ] Recently, it is reported that tuning atomic‐scale spacing between two facets of Cu NPs also attains the high activity and selectivity of C 2+ products in CO 2 RR. [ 185 ] Consequently, summarizing catalytic properties of different surface sites of catalysts is beneficial to identify active centers and further develop rational design strategies for highly efficient photocatalysts.…”
Section: Mechanism Of Localized Surface Plasmon Resonance‐mediated Reactions For Cu‐based Photocatalystsmentioning
confidence: 99%
“…Oxidation of CO 2 RR intended copper electrodes yields various types of nanostructures depending on method, process conditions and oxidizing agents. As it was reported, nanowires (NW) [91,92], nanoneedles (NN) [93], nanocrystals (NC) [94,95], and nanoparticles (NP) [96,97] of copper oxides and/or hydroxides can be produced during OD-Cu catalyst preparation. Gao et al [98] reported ECSA of O 2 -plasma oxidized Cu that was 44 times larger than parent Cu flat foil after 1 h of CO 2 RR.…”
Section: Electrochemical Co 2 Reduction Reactionmentioning
confidence: 97%